Analysis of land-use and livelihood transformations in peri-urban areas: Insights from North-Western Ghana - Alfred Toku; Samuel Twumasi Amoah; Nelson Nyabanyi N-yanbini; Anthony Kwabena Sarfo; Prosper Tornyeviadzi (Heliyon, 2024)
This paper questions claims that peri-urbanization perpetuates the shrinking of livelihood opportunities. A critical analysis of the peri-urbanization process presents a more nuanced transformation of livelihood opportunities. Drawing on concurrent triangulation mixed-method, primary data was sourced from non-farm workers using survey questionnaires, informant interviews, and observation from 225 respondents in a Ghanaian peri-urban community -Bamahu. Digital image software, Erdas Imaging 2015 and Landsat satellite were used to acquire land use and land cover data to affirm spatial differences. Quantitative data were analyzed using descriptive statistics complemented with thematic analysis for qualitative data. The findings showed significant land use and land cover alterations from 2000 to 2019. These changes resulted in the springing up of non-farm livelihoods that populated formal and informal non-farm opportunities. The analysis provides evidence that supports two key contributions to peri-urbanization and livelihood transformation debates. Empirically, it brings in-depth insights from original fieldwork data to highlight specific contextual realities by not only revealing the spatial alterations but also peering into how emerging non-farm livelihoods trade-off with existing farm-based livelihoods. Theoretically, it extends the debate by reframing peri-urbanization as a process of transforming livelihoods that thrive due to infrastructural development, new skills, and a ready market for goods and services. These findings have important implications for opening up a theorization of the peri-urbanization phenomenon. This paper concludes that the emergence of these livelihoods is crucial and should be adequately integrated into urban policies and plans to ensure inclusive cities.